CHRONOLOGY OF THE ROMANIAN POLITICAL LIFE, APRIL 01 – SEPTEMBER 30, 2024 (Studia Politica. Romanian Political Science Review, 2025)
Under the coordination of Domnica Gorovei, Teodora Lovin and Alexandru Găzdaru, the following students of the Faculty of Political Science, University of Bucharest, have contributed to the chronology (press monitoring and/or translation): Bălan Oana Doriana,Cosma Anca-Mălina, Iacob Maria Matilda, Teodor Andreea, Tivdă Radu-Alexandru, and Vasiliu Diana. The main sources of information used were the online editions of: Mediafax, RFI România, Agerpres, Spotmedia, Biziday, Digi24, Revista 22, G4Media, Romania-Insider.com, Press One.